A note on the Dutch disease - Heijman, Wim (Applied Studies in Agribusiness and Commerce, 2019)
Many resource rich countries are poor, where many resource poor countries are rich. One of the possible explanations of this paradox called the ‘resource curse’ is the Dutch Disease. This paper aims to analyse this phenomenon with the help of a simple macroeconomic trade model. It presents a number of Dutch Disease Cases of which the ‘Norwegian Case’ provides an example containing an effective policy against the negative impact of Dutch Disease on the national economy. JEL Classification: O11, O24, Q33